Facultad del lenguaje: la “hipótesis de solo ensamble” y la especificidad de dominio - Skidelsky, Liza (2018)
“Faculty of Language: the ‘Assembly-Only Hypothesis’ and Domain Specificity”. The faculty of language was always considered as the paradigm of a cognitive capacity that illustrates the property of domain specificity. In the minimalist-biolinguistic approach, this property seems to blur. However, the reason usually cited (for example, universal grammar is now “less rich”), does not seem adequate from the point of view of the conceptual coherence of the notion of domain specificity. In this paper I will distinguish between a sense of specificity of domain that is interesting  or useful for cognitive research and another vacuous one.I will show that if the analysis of the notion of domain specificity is conceptually coherent and the available empirical evidence is accepted, then these constitute the reasons why domain specificity cannot be attributed to the faculty of language under the assembly-only hypothesis.